Decellularised conjunctiva for ocular surface reconstruction. (February 2018) - Witt, Joana; Mertsch, Sonja; Borrelli, Maria; Dietrich, Jana; Geerling, Gerd; Schrader, Stefan; Spaniol, Kristina
Graphical abstract: Abstract: Conjunctival reconstruction is an integral component of ocular surface restoration. Decellularised tissues are frequently used clinically for tissue engineering. This study identifies porcine decellularised conjunctiva (PDC) and human decellularised conjunctiva (HDC) as promising substitutes for conjunctival reconstruction. PDC and HDC were nearly DNA-free, structurally intact and showed no cytotoxic effects in vitro, which was confirmed by DNA quantification, histology, transmission electron microscopy, collagen quantification and cytotoxicity assay. Comparing the biomechanical properties to amniotic membrane (AM), the most frequently applied matrix for ocular surface reconstruction today, the decellularised conjunctiva was more extensible and elastic but exhibited less tensile strength. The in vivo application in a rabbit model proofed significantly enhanced transplant stability and less suture losses comparing PDC and HDC to AM while none of the matrices induced considerable inflammation. Ten days after implantation, all PDC, 4 of 6 HDC but none of the AM transplants were completely integrated into the recipient conjunctiva with a partially multi-layered epithelium. Altogether, decellularised conjunctivas of porcine and human origin were superior to AM for conjunctival reconstruction after xenogeneic application in vivo . Statement of Significance: Conjunctival integrity is essential for a healthy ocular surface and clear vision. Its reconstruction is required in case of immunological diseases, after trauma, chemical or thermal burns or surgery involving the conjunctiva. Due to limitations of currently used substitute tissues such as amniotic membrane, there is a need for the development of new matrices for conjunctival reconstruction. Decellularised tissues are frequently applied clinically for tissue engineering. The present study identifies porcine and human decellularised conjunctiva as biocompatible and well tolerated scaffolds with superior integration into the recipient conjunctiva compared to amniotic membrane. Decellularised conjunctiva depicts a promising substitute for conjunctival reconstruction in ophthalmology.